DOUBLE-BLIND RANDOMIZED CLINICAL TRIAL OF KAEMPFERIA GALANGA L EXTRACT AS AN ANTI-INFLAMMATION (PROSTAGLANDIN E2 AND TUMOR NECROSIS FACTOR ALPHA) ON OSTEOARTHRITIS - NURPUDJI A TASLIM; M NATSIR DJIDE; YUSNITA RIFAI; AKMAL NOVRIAN SYAHRUDDIN; YOSEFA RIA RAMPO; MURNI MUSTAMIN; SIGIT ANGRIAWAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this study was to compare the effectiveness of the rhizome extract against inflammatory markers such as tumor necrosis factor (TNF)-alpha and prostaglandin E2 (PGE2) with meloxicam in patients with osteoarthritis at knee. Materials and Methods: This study designed two phases as follows: The preparation of rhizome extract in a capsule dosage form which was then followed by double-blind clinical trials, randomized controlled, pre- and post-test design (18 cases) using the WOMAC scores for pain, to markers of inflammation using an enzyme-linked immunosorbent assay method. Results: The results did not reveal any significant differences in pain scores, stiffnesses, and physical function impairment between the intervention (the rhizome extract) and control groups (meloxicam), it either did not reveal any significant differences in the parameters of inflammatory marker TNF alpha and PGE2 among the groups. Conclusion: The rhizome extract had the same effect on pain, stiffness, physical interference as meloxicam, and on PGE2 as well as on the inflammatory marker TNF-alpha. Therefore, this extract can be used as an alternative herbal medicine for osteoarthritis.